Characterization of the cell-mediated immune response to Takeda's live-attenuated tetravalent dengue vaccine in adolescents participating in a phase 2 randomized controlled trial conducted in a dengue-endemic setting. Issue 8 (16th February 2022) - Tricou, Vianney; Gottardo, Raphael; Egan, Michael A.; Clement, Frédéric; Leroux-Roels, Geert; Sáez-Llorens, Xavier; Borkowski, Astrid; Wallace, Derek; Dean, Hansi J.
Highlights: We characterized the T-cell responses elicited by TAK-003 against DENV non-structural proteins. Observed CD4+ and CD8+ T-cell responses were cross-reactive and multi-functional. Responses were observed irrespective of pre-vaccination DENV neutralizing antibodies. CD8+ responses were of greater magnitude than the CD4+ responses. Abstract: Background: As robust dengue-specific CD4+ and CD8+ T cell responses are essential for protective immunity, we assessed cell-mediated immune (CMI) responses to a DENV-2-based dengue tetravalent vaccine candidate (TAK-003) in adolescents living in Panama, a dengue-endemic country. Methods: Peripheral blood mononuclear cells were collected from a subset of 67 participants ≥ 10 years old included in a phase 2 clinical trial of TAK-003 (Clinicaltrials.gov: NCT02302066). Following stimulation with dengue peptides, the frequency, magnitude, and cross-reactivity of the CD8+ and CD4+ T cell IFN-γ, TNF-α and IL-2 responses were assessed by flow cytometry. Results: Intracellular cytokine staining identified NS1, NS3, and NS5 as the most common non-structural (NS) targets of the CD4+ T-cell response (IFN-γ+); NS3 and NS5 were the main NS targets of the CD8+ T cell response (IFN-γ+). Both CD4+ and CD8+ T-cell responses were multi-functional (IFN-γ + TNF-α + IL-2+) and cross-reactive against DENV-1, -3, and -4 serotypes. Similar responses were seen in all CMI assessments irrespective of participant baseline status for dengue neutralizing antibodies and T cells. Conclusions: TAK-003 elicited cross-reactive, multi-functional CD4+ and CD8+ T-cell responses, irrespective of dengue pre-exposure.